Comparison of the Effectiveness of Short-Term Psychodynamic Therapy and Mentalization on Self-Control in Individuals with Borderline Personality Structure - Majdi, Nasibeh; Taher, Mahboobe; Haj Aboutalebi, Narges (Mental Health and Lifestyle Journal, 2026)
The present study aimed to compare the effectiveness of short-term psychodynamic therapy and mentalization-based therapy on self-control in individuals with a borderline personality structure. The research employed a quasi-experimental design with a pretest–posttest control group and a 2-month follow-up. The statistical population included all individuals with borderline personality structure who referred to clinics in the western districts of Tehran during the second half of the year 2024 (October to March). From this population, 45 participants were selected using purposive sampling and randomly assigned into three groups (two experimental groups with 15 participants each and one control group with 15 participants). The assessment tools included the Personality Organization Questionnaire developed by Kernberg (2002) and the Self-Control Scale by Tangney et al. (2004). The first experimental group received mentalization-based therapy following the Bateman and Fonagy (2016) protocol, while the second experimental group received intensive short-term dynamic psychotherapy based on Davanloo’s (1995) protocol. Both interventions consisted of nine weekly 90-minute sessions. Data analysis was conducted using repeated measures analysis of variance (ANOVA). The results showed that both short-term psychodynamic therapy and mentalization-based therapy had a significant effect on self-control in individuals with borderline personality structure (p < .01). Moreover, no significant difference was found between the two therapeutic approaches in terms of effectiveness (p > .05). It can be concluded that both short-term psychodynamic therapy and mentalization-based therapy may be applied as effective therapeutic approaches to improve self-control in individuals with borderline personality structure.